Immunohistological analysis of extracted anterior cruciate ligament graft impinged against posterior cruciate ligament - Kato So; Fukai Atsushi; Takeda Hideki; Taketomi Shuji; Nakayama Shuichi; Hirota Jinso; Nakajima Kohei; Nakamura Kozo; Nakagawa Takumi (BMC, 2011)
Abstract A young female athlete suffered from the residual instability of the knee after anterior cruciate ligament (ACL) reconstruction with hamstring autograft. The 3-dimensional (3-D) CT scan showed the "high noon" positioning of the primary femoral bone tunnel. The revision surgery with anatomic double-bundle technique was performed two years after the primary surgery and the femoral tunnels were created with the assistance of the 3-D fluoroscopy-based navigation. An arthroscopic examination confirmed the ACL graft impingement against posterior cruciate ligament (PCL) when the knee was deeply flexed. The histological analysis of the resected primary ACL graft showed local inflammatory infiltration, enhanced synovial coverage and vascularization at the impinged site. The enhanced expression of vascular endothelial growth factor (VEGF) at the impinged area when compared with non-impinged area was observed on immunohistochemical analysis. Abnormal mechanical stress by the impingement against PCL might have induced chronic inflammation and VEGF overexpression.